The United States Department of Commerce a story of industry, science, and trade - Terrell, John Upton 1900-1988 (Duell, Sloan and Pearce, 1966)
Describes the work of the Department of Commerce in the following areas: shipping, patents, weather, roads, depressed areas, navigation, measurement, and business
Keywords: United States / Dept. of Commerce; USA